Twitter Mentions of February 6th Earthquake: An Emotional Language Analysis - Uzun, Cemile (Istanbul Univ, 2023)
Social media is crucial during and after earthquakes, as it enables people to both receive information and express themselves. This study focuses on the analysis of the emotional language used by people when sharing their experiences related to the earthquake that occurred in Turkey on February 6, 2023. In the current study, the emotional language analysis focused on the social media tool Twitter alone. Emotion analysis is a natural language processing technique used to identify emotions expressed in a text. The current study aims to reveal the reflection of emotions about the earthquake in specific expressions and the variation in these emotions over time. For this purpose, an emotional language analysis of tweets posted on Twitter with the hashtag #earthquake between February 6 and June 6 was conducted. Nakamura's system of emotion analysis was used to perform the emotional language analysis. In his work Kanjo hyogen jiten (Dictionary of emotive expressions), Nakamura emphasized ten classifications of emotions: excitement, embarrassment, joy, fondness, dislike, sadness, anger, surprise, fear, and relief. From these, six emotions, namely joy, grief, anger, surprise, fear, and relief, were selected to analyze the emotional language in tweets about the earthquake. Our study is distinct from other studies in Turkey in terms of both revealing the emotional language resulting from the earthquake and using Nakamura's emotion analysis.
Keywords: Earthquake; 6th February; Kahramanmaras; Emotion analysis; Language